Technopreneur sebagai Jembatan Masa Depan bagi Anak Panti Asuhan Riyaadlul Jannah Semarang - Almira Santi Samasta; Febrianur Ibnu Fitroh Sukono Putra; Diana Aqmala; Dandy Aprilya (Lembaga Pengembangan Kinerja Dosen, 2025)
The children of the Riyaadlul Jannah Orphanage are assets that need to be directed to be able to adapt to living conditions in order to become independent and responsible individuals. One solution to increase independence that can be done for children in orphanages is to become an entrepreneur, this is because business activities are flexible and are an alternative source of sustenance provided by Allah SWT. Limited ideas, mental readiness and capital are obstacles for children in orphanages to start their businesses, so that they are less able to achieve economic independence. E-commerce is an alternative solution for starting an entrepreneur while utilizing technology to achieve economic independence more effectively and efficiently. Ease of access, use and relatively affordable costs mean that children in orphanages can start businesses more quickly, thus making it easier for orphanages to ensure their livelihoods. This service program aims to develop community groups at the Riyaadlul Jannah Orphanage to become economically independent, help create peace, comfort in social life, and improve skills in digital entrepreneurship. The approach method used includes the FGD (Focus Group Discussion) approach including sharing sessions. The activity stages consist of preparation, investigation, implementation and evaluation stages. The results of this activity, among other things, show that the orphanage children have an understanding of e-commerce, have business ideas, marketplaces as stalls, and are interested in starting a business immediately.